Illocutionary Acts and Progressive Education Values in Public Opinion Against Violence on Twitter base Account @Askrlfess - Faradila, Divia; Markhamah, M (Universitas Muhammadiyah Surakarta, 2023)
Purpose : This research aims to: 1) identify types of illocutionary speech acts in public opinion regarding violence on the base Twitter account @Askrlfess; 2) identify the value of progressive education in public opinion against violence on the base Twitter account @Askrlfess; and 3) the relevance of public opinion on violence on the Twitter base account @Askrlfess in Indonesian language learning. Methodology: This type of research is qualitative research. The research method used in this research is a descriptive method with a qualitative approach. The data collection technique in this research uses reading and note-taking techniques. The data credibility test was carried out by data triangulation. The data analysis technique in this research uses intralingual matching and pragmatic matching methods. Results: The results of this research were speech in public opinion regarding violence on the Twitter base account @Askrlfess: 1) 58 forms of illocutionary speech acts were found; 2) there are 4 values of progressive education contained in public opinion against violence on the base Twitter account @Askrlfess, and 3) speech in public opinion against violence on the base Twitter account @Askrlfess has relevance to Indonesian language learning material, namely response texts.